Pembelajaran Pedagogik Futuristik - Budiyono, Slamet; Kurniawati, Wakhidah (Lembaga Yasin AlSys, 2024)
Education continues to experience dynamic development and is related to both philosophical and practical aspects, so that education will continue to experience development and re-deconstruction, in accordance with these fundamental needs and values required. This article aims to try to explore various possibilities that will occur in the future, with the philosophical value of futuristic pedagogy which contains aspects whose urgency does not contradict the needs that students must have in the future. In addition, the curriculum initiated by the Ministry of Education and Culture is related to the independent curriculum, which has the feel of freedom for students and teachers, for teachers as providers of learning materials or for students as recipients of learning. The problem that occurs in education today, there are many students who fall into the snare of disorientation, so that many students do not have and optimize what are the advantages and talents they have, education that does not optimize and develop the fundamental aspects possessed by students will not able to make students survive in the future, with increasingly complicated problems. Therefore, the presence of futuristic pedagogy can be realized in an educational climate and not become an ivory tower concept.